Clinical, cytogenetic and molecular genetic characterization of a tandem fusion translocation in a male Holstein cattle with congenital hypospadias and a ventricular septal defect. - Alessandra Iannuzzi; Marina Braun; Viviana Genualdo; Angela Perucatti; Sina Reinartz; Ioannis Proios; Maike Heppelmann; Jürgen Rehage; Kirsten Hülskötter; Andreas Beineke; Julia Metzger; Ottmar Distl (PLoS ONE)
Hypospadias, disorder of sex development (DSD), is a sporadic congenital abnormality of the genital region in male ruminants, which is characterized by a non-fused urethra during fetal development. Detailed clinical examination classified the hypospadias phenotype of a male Holstein calf studied here as the perineal type. In combined use of cytogenetic analysis and whole genome sequencing, a non-mosaic, pseudo-monosomy 59, XY + tan(18;27) was detected. This chromosomal aberration had its origin in a tandem fusion translocation of the bovine autosomes (BTA) 18 and 27 with an accompanying loss of genomic sequences mainly in the distal end of BTA 18 and the proximal end of BTA 27. The resulting phenotype included hypospadias, growth retardation and ventricular septal defect.